Contracts, Price Rigidity, and Market Equilibrium - Carlton, Dennis W. (Journal of Political Economy, 1979)
This paper presents a model of a market characterized by uncertainty and transaction costs. The uncertainty and transaction costs create incentives for firms to use both long- and short-term fixed-price contracts. The model sheds light on several puzzling empirical observations. I explain why long-term-contract prices can move by different magnitudes and even in different directions than short-term prices, why econometric price equations are likely to find costs, but not demand forces, mattering, and why "rigid" prices and delivery lags are not necessarily disequilibrium phenomena but, rather, can be perfectly understandable and predictable equilibrium phenomena.